2020
DOI: 10.20546/ijcmas.2020.903.286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moisture Regime on IW/CPE Ratio on Soil Properties, Yield and Water use Efficiency of Wheat Crop (Triticum aestivum L.)

Abstract: Wheat (Triticum aestivum L.) is one of the most important cereal crop of the world. Among the world's most important food grains, it ranks next to rice. It is eaten in various forms by more than one billion in the world. India is the second largest producer of wheat in the world. In India production was 97.44 million tons from an area of 30.73

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
0
0
Order By: Relevance
“…All the growth, yield attributes and yield are significantly superior under irrigation schedule I 1 (IW: CPE= 1.0) probably because of the increased water availability in the root zone which resulted in absorption of nutrients from the soil and ultimately gives vigorous growth and reproductive capacity of the wheat. This finding is in conformity with Salunkhe et al [18], Verma et al [19], Deo et al [20], Pal et al [21,22] and Gajbhiye [23] also reported similar results.…”
Section: Effect Of Irrigation Schedulessupporting
confidence: 92%
“…All the growth, yield attributes and yield are significantly superior under irrigation schedule I 1 (IW: CPE= 1.0) probably because of the increased water availability in the root zone which resulted in absorption of nutrients from the soil and ultimately gives vigorous growth and reproductive capacity of the wheat. This finding is in conformity with Salunkhe et al [18], Verma et al [19], Deo et al [20], Pal et al [21,22] and Gajbhiye [23] also reported similar results.…”
Section: Effect Of Irrigation Schedulessupporting
confidence: 92%
“…Also, lack of moisture resulted in less dry matter accumulation. Pal et al [30] also observed less dry matter accumulation due to the lack of moisture. Deo et al [31], Chouhan et al [32] and Buttar et al [21] also observed similar results.…”
Section: Relative Growth Rate (G M -2 Day -1 )mentioning
confidence: 91%
“…"Significant effect of irrigation (0.7 IW: CPE ratio) on growth and yield of mustard" [18]. "Application of (I4)1.0 IW/CPE ratio moisture regime found to be more suitable higher yield of wheat variety PBW -154" [19].…”
Section: Irrigation Water (Iw) / Cumulative Pan Evaporation (Cpe) App...mentioning
confidence: 99%